2009
DOI: 10.1038/mp.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and genetic studies identify IL-33 as a candidate gene for Alzheimer's disease

Abstract: The only recognized genetic determinant of the common forms of Alzheimer's disease (AD) is the e4 allele of the apolipoprotein E gene (APOE). To identify new candidate genes, we recently performed transcriptomic analysis of 2741 genes in chromosomal regions of interest using brain tissue of AD cases and controls. From 82 differentially expressed genes, 1156 polymorphisms were genotyped in two independent discovery subsamples (n = 945). Seventeen genes exhibited at least one polymorphism associated with AD risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
176
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(184 citation statements)
references
References 47 publications
4
176
1
3
Order By: Relevance
“…They found protective effects of rare alleles of three intronic SNPs (rs7044343, rs1157505, and rs11792633) and the associated haplotypes [36]. In addition, functional analyses have revealed interactions between these protective allele and decreased cerebral amyloid angiopathy in the brains of non-APOE e4 individuals with AD [36]. Subsequently, consistent results for rs11792633 were obtained in a Han Chinese population; however, rs7044343 failed to affect AD risk, and the rs1157505 polymorphism was not observed [102].…”
Section: Other Pro-inflammatory Cytokinessupporting
confidence: 54%
See 3 more Smart Citations
“…They found protective effects of rare alleles of three intronic SNPs (rs7044343, rs1157505, and rs11792633) and the associated haplotypes [36]. In addition, functional analyses have revealed interactions between these protective allele and decreased cerebral amyloid angiopathy in the brains of non-APOE e4 individuals with AD [36]. Subsequently, consistent results for rs11792633 were obtained in a Han Chinese population; however, rs7044343 failed to affect AD risk, and the rs1157505 polymorphism was not observed [102].…”
Section: Other Pro-inflammatory Cytokinessupporting
confidence: 54%
“…A study by Chapuis et al initially identified the association between IL-33 polymorphisms and AD risk in Caucasian populations. They found protective effects of rare alleles of three intronic SNPs (rs7044343, rs1157505, and rs11792633) and the associated haplotypes [36]. In addition, functional analyses have revealed interactions between these protective allele and decreased cerebral amyloid angiopathy in the brains of non-APOE e4 individuals with AD [36].…”
Section: Other Pro-inflammatory Cytokinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiopoietins have important roles in vascular development and angiogenesis, and disturbances in this process can result in a range of diseases, such as agerelated blindness, cancer and stroke. 71,72 Chapuis et al 73 have shown, by performing a transcriptomal analysis of brains followed by SNP genotyping in the differentially expressed genes, that six SNPs in ANGPT4 were associated with AD. A 65% difference in gene expression was found between the brains of AD and controls.…”
Section: Discussionmentioning
confidence: 99%